Role of quenching method on cooling rate and microstructure of steels: Variations in coolant and its flow arrangement - Lee, Sang Gun; Kaviany, Massoud; Lee, Jungho (International Journal of Heat and Mass Transfer, 2022)
During quenching of steel, the rate of heat removal from the surface and the local cooling rate of steel determine its microstructure. Here these rates are controlled by the extent of the force flow (e.g., single and multiple jets, forced and unforced immersion), coolant (e.g., water and oil), and steel (e.g., stainless or alloy). The steel plate is initially at 900°C is cooled with room-temperature coolants. The recorded temperature distribution within the object is used to compute the surface temperature and heat flux by solving the inverse heat conduction problem (IHCP). The high Biot number analytic solution of 1-D transient conduction in semi-infinite slab with prescribed surface temperature is also used as a reference for the ideal cooling condition. It is shown that the multiple water jet cooling results in the highest heat transfer rate (largest Biot number) and cooling rate, thus the desired martensite phase of the microstructure. On the other hand, the water forced immersion, water immersion, and oil immersion have a progressively lower cooling rate (smaller Biot number), and therefore, a smaller fraction of the martensite phase. Comparison of the IHCP and analytic results for the multiple water jets show that the IHCP underpredicts the cooling rate for the first 0.5 s.
Keywords: Biot number; Cooling rates; Inverse heat conduction problem; Jet quenching; Martensite phasis; Multiple jet quenching; Multiple jets; Theoretical approximations; Various quenching method; Waterjets; Inverse heat conduction problem; Microscopic examination; Multiple jet quenching; Theoretical approximation; Various quenching methods